Influence of the charge carrier contribution on the dielectric permittivity of a LiTaO3-type crystal - Dong, M; Reau, JM; Ravez, J; Joo, G; Hagenmuller, P (GORDON BREACH SCI PUBL LTD, 1997)
A dielectric response relation is proposed to differentiate the lattice response from the charge carrier response in ferroelectric materials. This relation may be considered as a generalization of the Cole-Cole dielectric expression. It is applied to a LiTaO3-type single crystal.